Pengaruh Pembelajaran Biologi Berbasis Problem Based Learning Terintegrasi Nilai Iskam Terhadap Kemampuan Berpikir Kritis Siswa Kelas X Madrasah Aliyah Negeri 1 Halmahera Selatan - Roni Daud; Ade Haerullah; Bahtiar Bahtiar; Rauf Yusuf (Peneliti.net, 2023)
Problem Based Learning integrated with Islamic values ​​in biology learning is one of the innovative contextual learning designs that can encourage students in learning biology related to Islamic values ​​to train students' mindsets to be more critical in solving problems in learning biology. The purpose of this study was to determine the effect of Biology teaching materials based on Problem Based Learning integrated with Islamic values ​​on the critical thinking skills of class X students at Madrasah Aliyah Negeri (MAN) 1 South Halmahera. This research is a quasi-experimental research (Quasy Experiment). The research sample consisted of two classes, namely class X-A as the experimental class and X-B as the control class with a total of 43 students. The instrument used is a test to measure students' critical thinking skills. Data analysis used SPSS-assisted normality and homogeneity tests while hypothesis testing used the Anacova test. The results showed that problem-based learning-based biology learning integrated with Islamic values ​​had an effect on the critical thinking skills of students of class X at Madrasah Aliyah Negeri (MAN) 1 South Halmahera with a significant grade of 0.003 > 0.05.